Effects of 12-week Pilates training program on cardiac autonomic modulation: A randomized controlled clinical trial - Cavina, Allysiê Ps [UNESP] (2021)
Aim: To evaluate the effects of 12-week Pilates training program on cardiac autonomic modulation. Materials & methods: A randomized controlled trial of a 12-week Pilates training program was conducted. A total of 54 men were randomly allocated to either a control or a Pilates group. Initially, the RR intervals were captured for 20 min for later analysis of heart rate variability (HRV). The training protocol was then initiated, in which the Pilates group performed 36 sessions of the Pilates method for approximately 60 min each session, three-times a week, totaling 12 weeks. The control group was instructed to maintain their normal activities during this period. One week after the end of the training, the final evaluations were performed with the capture of RR intervals in both the groups. Linear indices in the time (SDNN and rMSSD) and frequency (low frequency [LF] and high frequency [HF]) domains, and the Poincaré plot (SD1 and SD2) were used. Nonlinear indices were also analyzed (approximate entropy and detrended fluctuation analysis). Descriptive statistics and generalized mixed models were performed. Results: There was a group effect for LF (ms) and a time effect for SD2. There was a training effect observed by the time*group interactions in which an increase in global HRV indices was found for the Pilates group after 12 weeks (SDNN: mean difference [MD] = 9.82; standard deviation [SD] = 18.52; ES = -0.514; LF [ms]: MD = 334.23; SD = 669.43; ES = -0.547; SD2: MD = 14.58; SD = 24.28; ES = -0.693). Conclusion: A 12-week Pilates training program promotes significant improvement in global modulation of HRV in the Pilates group considering the significant increase in SDNN, LF (ms) and SD2 indices. Trial registration number: NCT03232866.